Six leviers pour améliorer l’apprentissage des étudiants du supérieur - Marianne Poumay (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Based on reports established by 200 university teachers at the University of Liège, and also inspired by scientific literature on teaching and learning in higher education, this article presents six forms of actions that can potentially act as leverages for educational innovation. From these 6 levers, we then analyze a particular innovation, which is the introduction of a tool for ‘individual management of skills’ in a program for speech therapists at the University of Liège. The article discusses adjustments made for the following academic year, including pedagogical and organizational aspects, as well as some research lines. The conclusion emphasizes the role of these levers, the use of which is not a guarantee of successful innovation, but rather a driving force supporting change in a course or program that focuses on students’ learning.